The Characteristics and The Making of Biopolymer Film from Oil Palm Trunk Starch (Elaeis guineensis Jacq.) Using Sorbitol Plasticizer - Hamzah, Amir (Talenta Publisher, 2019)
The research about of the biopolymers film from oil palm trunk starch had been done. Biopolymers film made by mixing of oil palm trunk starch (Elaeis guineensis Jacq.) and plasticizer sorbitol with the variation was 2:0,8 ; 2:1,0 ;2:1,2 (g/mL), then the film was molded on acrylic plate and dried in an oven at 40Â°C for 24 hours. The results of the film characterization show that the best variation of biopolymers on comparison 2:0,8 (g/mL) with the value of tensile strength was 4,26 MPa, percentage of elongation was 1,87 %, and film thickness was 0,16 mm, then it can be used as reference for addition 2 gram chitosan on the establishment of biopolymer film. It was characterized by tensile strength test with value was 14,00 MPa, pencentage of elongation with value was 3,20 %, and film thickness with value was 0,10 mm. The results of Differential Scanning Calorimetry (DSC) showed increasing of the endothermic temperature was 115,75 oC and exothermic temperature was 394,56 oC. The results of Thermal Gravimetry Analysis (TGA) showed that at a temperature of 340,1 0C the film to start decomposed. The value of % Swelling was 63,176%. The Fourier Transform Infra Red (FT-IR) result showed that in biopolymers film occurs physical interaction only. As well as, the antibacterial activity analysis showed that addition of chitosan on biopolymer film made Staphylococcus Aureus and Escherichia Coli bacterial was great inhibited with index antibacterial value of 0,625 respectively. From SEM analysis showed that film had been added by chitosan more homogenous than film without chitosan addition. The presence of chitosan addition tend to increase the physical and mechanical properties of biopolymer film.